Usefulness of the newly developed artificial denture plaque for practical denture care training - Katsuya Kawanishi; Tomoe Okahashi; Hideki Aita; Yuki Kan; Masao Yamazaki; Kenya Asahiro; Shizue Oyama; Takumi Ueki; Kana Sugihara; Riyo Chiba; Masa Yamagata; Kunio Matsubara; et al. (Wiley, 2020)
Abstract Objectives The aim of this study was to investigate whether the newly developed artificial dental plaque (A‐DP) is useful as an educational tool for denture care of dental hygienist that compared it with conventional artificial dental plaque from the viewpoint of practical skills. Material and methods The 125 dental hygienist school students and 26 dental hygienists who had clinical experience were subjected a practical training of denture plaque control using the conventional denture plaque (C‐DP) and the A‐DP. The questionnaires based on the semantic differential method were used to survey whether the A‐DP is similar to the real denture plaque (R‐DP). Factor analysis by rotation of promax was carried out. Results In the results of the factor analysis, the two factors could be detected in students and three factors in dental hygienists. The total score of each denture plaque was calculated for each factor, and correlation coefficient was examined. There was significant correlation between the A‐DP and the R‐DP at the first factors, both students and dental hygienists. C‐DP was not similar to R‐DP in all factors. Conclusions These results suggested that A‐DP resembles R‐DP better than C‐DP. It was concluded that the A‐DP was similar to the R‐DP and could be a potent educational tool for practical denture care.